Re-evaluation of cancer incidence for gender in Genetics Iraq - Noah A. Mahmood; N.A Thamer (Iraqi Journal of Cancer and Medical Genetics, 2019)
There has been a rapid increase in the number of computed tomography (CT) scans which utilized for the purpose of disease diagnosis. The radiation exposure can increase the probability of developing different type of cancers. This prospective study was carried out in the Computed Tomography Unit of Al-Imamain Al-Kadhimain Medical City and Al-yarmok teaching hospital in Baghdad Iraq in the period from 1 January to 31 October2018. About 3,758 adult patients (1743 male and 2015 female) with their age ranging from (10-79) who received a CT scan for different site of the body participate in this study. The main results obtained showing that the CT radiation correlated with the age and sex of the patient, with higher risks be expected of thyroid cancer among patients who were younger and female.